Hamilton Harbour Remedial Action Plan process: Connecting science to management decisions. Issue 2 (2nd April 2016) - Hall, John D.; O'Connor, Kristin M.
Abstract : Hamilton Harbour is located at the western end of Lake Ontario and was designated an Area of Concern in 1985. The Stakeholder process consistently followed by the Hamilton Harbour Remedial Action Plan since the mid-1980s has been identified as one of the best methods for integrating science, public input, and management. Using examples from this Remedial Action Plan, connections between science and remedial actions are examined along with the relationship of science to the public and political decision makers. A case study in wastewater decisions in Hamilton Harbour is offered as an example of how the planning and management process integrated and used science to define and refine remedial actions. Important lessons about community values, communication, and timing are highlighted.